GEOCHEMICAL EVALUATION OF CRUDE OILS FROM THE CARACARA AND TIPLE AREAS, EASTERN LLANOS BASIN, COLOMBIA: PALAEO BIODEGRADATION AND OIL MIXING. (13th March 2018) - Esquinas, N.; Márquez, G.; Permanyer, A.; Gallego, J.R.
Abstract : This study presents an organic geochemical characterization of heavy and liquid oils from Cretaceous and Cenozoic reservoir rocks in the Tiple and Caracara blocks in the eastern Llanos Basin, Colombia. Samples of heavy oil were recovered from the Upper Eocene Mirador Formation and the C7 interval of the Oligocene – Miocene Carbonera Formation; the liquid oils came from these intervals and from the Cretaceous Guadalupe, Une and Gachetá Formations. The heavy oil and most of the liquid oils probably originated from multiple source rocks or source facies, and showed evidence of biodegradation as suggested by the coexistence of n‐alkanes and 25‐norhopanes. The results indicate a close genetic relationship between the samples in the Carbonera (C7 interval), Mirador and Guadalupe Formation reservoirs. These petroleums are interpreted to result from at least two separate oil charges. An early charge (Oligocene to Early Miocene) was derived from marine carbonate and transitional siliciclastic Cretaceous source rocks as indicated by biomarker analysis using GC/MS. This initial oil charge was biodegraded in the reservoir, and was mixed with a later charge (or charges) of fresh oil during the Late Miocene to Pliocene. A relatively high proportion of the unaltered oil charge was recorded for heavy oil samples from the Melero‐1 well in the Tiple block, and is inferred to originate from Cenozoic carbonaceous shale or coaly source rocks. Geochemical parameters suggest that oils from the Gachetá and Une Formations are similar and that they originated from a source different to that of the other oil samples. These two oils do not correlate well with extracts from transitional siliciclastic source rock from the Upper Cretaceous Gachetá Formation in the Ramiriqui‐1 well, located in the LLA 22 block to the north. By contrast, one or more organofacies of the Gachetá Formation may have generated the heavy oil and most of the liquid oil samples. The results suggest that the heavy oils may have formed as a result of biodegradation at the palaeo oil‐water contact, although deasphalting cannot entirely be dismissed.